PENGARUH VARIASI WARNA KUNING PADA FLY GRILL TERHADAP KEPADATAN LALAT (STUDI DI TEMPAT PELELANGAN IKAN TAMBAK LOROK KOTA SEMARANG) Effect Of Variation The Color Yellow On Fly Grill To Density Of Flies (Study At Fish Ouction Place Tambak Lorok Semarang Cit - Dewi Agustina Wulandari; Lintang Dian Saraswati; Martini Martini (Jurnal Kesehatan Masyarakat (Undip), 2017)
Flies are vectors that carrying disease so need measured it densities for control purposes. Flies also the insects which have compound eyes can distinguish some colors frequencies. Fly grill one the tools measuring density of flies. Fly grill made wooden planks with varied color. Fly grill used given paint the ocher, light yellow, white and one fly grill without paint. The general objective of this study was determine the effect of variations of yellow color the fly grill to the density of flies. The study design used was quasi experiment with models Post Test Only Design. This research was conducted at the fish auction place (TPI) Tambak Lorok Semarang city for four days at four different locations. At predetermined point, did measurements ten times by calculating the average data five times the highest calculation. The results show the werage number of fly grill without paint is 8,5 flies, white 9,5 flies, ocher 16 ekor, light yellow 9,75 flies. Data were analyzed by Kruskall Wallis the significant level α=0.05. From the calculation using Mann Whitney, states that there are differences the density of flies the fly grill by using different color variations, in order from highest to lowest is ocher color, light yellow, white and without paint. Herefore, is advisable to use the fly grill with ocher colors in measuring the density of flies also the need for the control of flies in TPI because of the results from research obtained the flies have exceeded five flies per block grill.